Purchasing power parity in Mexico since 1933 - Frederick H. Wallace (Latin American Economic Review, 2017)
A new approach to cointegration developed by Enders et al. (Cointegration tests using instrumental variables with an example of the U.K. demand for money. Unpublished working paper. http://wenders.people.ua.edu/time-series-methods.html, 2008) is applied to long-span, high-frequency data to test for purchasing power parity in the Mexico-US real exchange rate. Overall the empirical results suggest that purchasing power parity (PPP) holds for the study period. The evidence for PPP is stronger when structural breaks are allowed in the real exchange rate.
Keywords: C22; F30; 330; Purchasing power parity; Real exchange rate; Cointegration